2019
DOI: 10.1039/c9dt02682g
|View full text |Cite
|
Sign up to set email alerts
|

Steric control of dioxygen activation pathways for MnII complexes supported by pentadentate, amide-containing ligands

Abstract: Steric control of dioxygen activation is demonstrated through O2 titration and isotopic labeling experiments for two Mn(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Fe II (Me 3 TACN)­(S 2 SiMe 2 ) serves as a platform to activate O 2 to generate a series of Fe/oxygen intermediates (Fe­(peroxo), Fe­(oxo), and Fe­(hydroxo) species), which could be trapped at low temperature and spectroscopically characterized (Scheme and Table ). This sequence of reactive species has been proposed in the activation of O 2 by iron and manganese complexes. ,, A crystallographically characterized thiolate-ligated Mn III –O–O–Mn III complex has been demonstrated to decay to an oxo-bridged Mn III –O–Mn III ; however, no Mn IV (O) species was identified . In addition, a similar thiolate-ligated Fe complex was shown to react with O 2 to form an Fe III 2 (μ-O) complex.…”
Section: Discussionmentioning
confidence: 99%
“…Fe II (Me 3 TACN)­(S 2 SiMe 2 ) serves as a platform to activate O 2 to generate a series of Fe/oxygen intermediates (Fe­(peroxo), Fe­(oxo), and Fe­(hydroxo) species), which could be trapped at low temperature and spectroscopically characterized (Scheme and Table ). This sequence of reactive species has been proposed in the activation of O 2 by iron and manganese complexes. ,, A crystallographically characterized thiolate-ligated Mn III –O–O–Mn III complex has been demonstrated to decay to an oxo-bridged Mn III –O–Mn III ; however, no Mn IV (O) species was identified . In addition, a similar thiolate-ligated Fe complex was shown to react with O 2 to form an Fe III 2 (μ-O) complex.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited reports on isolobal analogues of iron­(IV)-oxo species. However, Borovik and co-workers observed that the iron­(III)-imido complexes could be synthesized by intermolecular C–H abstraction by an iron­(IV)-species (Scheme ). The system was spectroscopically characterized and crystallographically trapped.…”
Section: Biomimetic Studies On First-coordination Sphere Effectsmentioning
confidence: 99%
“…contrast to acetonitrile [18] . This behavior can be attributed to the nature of the solvent coordination in the metal center, which is stronger in the case of DMF, and prevents the introduction of the O 2 in the coordination sphere of the Mn(II) [17d] .…”
Section: Resultsmentioning
confidence: 94%
“…DMF is a convenient solvent to study O 2 activation because Mn II -(dpaq)(OTf) does not react with O 2 spontaneously in DMF, in contrast to acetonitrile. [18] This behavior can be attributed to the nature of the solvent coordination in the metal center, which is stronger in the case of DMF, and prevents the introduction of the O 2 in the coordination sphere of the Mn(II). [17d] Two oxidation features (p 1 and p 1 0 ) and one reduction feature (p 1 0 0 ) are present.…”
Section: Resultsmentioning
confidence: 99%